Association between single nucleotide polymorphisms in EPAS1 and PPARA genes and high altitude polycythemia in Chinese Tibetan population - Chen, Ziyi; Dong, Zhaomei; Zeng, Rong; Xu, Mengna; Zhang, Yuanyuan; Dan, Qu; Wang, Guangming (Frontiers in Genetics, 2025)
BackgroundHigh altitude polycythemia (HAPC) is a disease with high morbidity and great harm in high altitude populations. It has been shown that Single Nucleotide Polymorphisms (SNPs) correlate with the genetic basis of adaptation to plateau hypoxia in Tibetan populations. The EPAS1 and PPARA genes are involved in hypoxia adaptation by encoding transcription factors in Tibetan populations at high altitude. The aim of this study was to investigate the association of EPAS1 and PPARA gene locus polymorphisms with genetic susceptibility to HAPC in the Chinese Tibetan population. Methods We included 78 HAPC patients and 84 healthy controls, and genotyped the EPAS1 gene SNP loci (rs6735530, rs6756667, rs7583392, and rs12467821) and PPARA rs6520015 by using TaqMan polymerase chain reaction. Logistic regression was used to analyze the association between these SNPs and HAPC; interactions between SNPs were also predicted by multifactorial dimensionality reduction (MDR) analysis.ResultsWe found that the PPARA rs6520015 polymorphism was not associated with the risk of HAPC in the Chinese Tibetan population; EPAS1 rs6735530, rs6756667, rs7583392, and rs12467821 increased the risk of HAPC in some models. Haplotype TCAGC decreases the risk of HAPC; Haplotype TTGAT increases the risk of HAPC; and EPAS1 rs7583392 is in complete linkage disequilibrium with rs12467821. The best prediction model was the EPAS1 rs6756667 unit point model, but the P value was greater than 0.05 in all three models, which was not statistically significant.ConclusionThe present findings suggest that among the Tibetan population in China, There is an association between EPAS1 rs6735530, rs6756667, rs7583392, and rs12467821 and the risk of HAPC, and that there is no significant correlation between PPARA rs6520015 and the risk of HAPC.